RESPIRATORY MUSCLES TRAINING (RMT) TO DYSPNEA SCALE OF COPD: A SYSTEMATIC REVIEW - Imron Rosyadi; Shinta Dewi Kasih Bratha (Universitas Islam Negeri Alauddin Makassar, 2021)
SummaryBackground: COPD can decrease patients' activity because of dyspneaObjectives: To critically evaluate the effect of RMT as a treatment of COPD.Method: Five databases were found from 2008, a randomized clinical trials (RCTs) research will be a reference if they evaluated RMT against any type of control in patients with any form of respiratory muscle weakness.Result: Five trials met the inclusion criteria. One journal has the good of sampling technic by using the COPD patient from 3 hospitals. Only four journals show the significant effect of RMT to decrease dyspnea of COPD. The impact of RMT is going to increase the lung capacity, lung function, activity, respiratory muscle straightness, and minimize the effort of breathing. Only one journal does this intervention for 12 weeks.Conclusion: The evidence for the effect of RMT to decrease the dyspnea scale has a significant impact. For future studies, it will be better to use RMT longer to get a more considerable impact.